Pasternak and Costello: What We Know and What We (Still) Don’t - Mancosu, Paolo (Wiener Slawistischer Almanach, 2021)
In this article I report on all the information I have been able to collect and discover concerning the contacts between Boris Pasternak and Desmond Patrick (“Paddy”) Costello. In each section, I begin by surveying the literature that was available to me when I began this investigation and then describe the new finds. The relation between Costello and Pasternak has been mainly emphasized by scholars interested in Costello. By contrast, Costello has only been rarely mentioned by Pasternak scholars. One of the reasons is that no document by Pasternak mentions Costello. However, Lazar Fleishman had already mentioned Costello’s work on The Oxford Book of Russian Verse as the source of the tamizdat phenomenon. In this paper, I give further evidence for Fleishman’s claim. Not only did Costello consult Pasternak for The Oxford Book of Russian Verse but by arranging the smuggling of an early version of Doctor Zhivago from Moscow to Oxford in 1948, he was the first link in a chain that would lead to the eventual publication of Doctor Zhivago in the West in 1957.